Using educational portfolios at university and educating in values (Praxis Educativa, 2012)
We agree with Gloria Ladson-Billings (1999) that the moral and ethical dimensions of teaching constitute “the missing entry” in educational portfolios. Nevertheless, years of experience in the implementation of such an instument of alternative assessment – continuous, formative and process-centred- in the subject English Language II at the Univrsity  of  La  Pampa s English  Teacher  Training  College  caused  our  inquiries  to  be focused  on  the  above dimensions.  From  an  outlook  on  teaching  and  evaluation  as humanistic, epistemological and ethical, in which our teaching and assessment practices are subjected to permanent scrutiny following the paradigm of participatory Action-Research, educating in values constitutes a component without which our work would lack sense and perspective. But, improved classes and assessment instruments are not enough for the betterment of students as integral educational subjects. The present work shows how, working with portfolios in a propitious context, students become assessors, redistributing and democratizing the exercising of a such a role, and develop attitudes of responsibility, reflection,  self-criticism,  cooperation, commitment,  solidarity,  tolerance  and  acceptance and integration of differences. We hold this genuinely means educating in values and contribute to the training of human resources professionally and ethically prepared to foster educational, social and moral change.
Keywords: educational portfolios; ethical and moral dimensions; educating in values; educational; social and moral change